Verbal and Non-Verbal Means in Creating Comic Effect - Saienko Anna Serhiivna (My University, 2020)
The theme of master’s paper is Verbal and non-verbal means of communication in expressing emotions in Great Britain and in the United States of America. The problem is that there is a need for a topic and proper study of verbal and non-verbal means of communication in foreign culture. The research of the comic as a linguistic category comes to the fore. The comedic devices and techniques are usually examined in English television, shows, movies and videos. The topicality is that people often say many things meaning serious ideas but listeners understand these words in a wrong way, they perceive it like comic action. The aim of master’s paper is to find out ways of expressing comic effect in verbal and non-verbal means of communication. Choosing the research object verbal and non-verbal communication which are used to create a comic effect, the subject of research defines analyses of the peculiarities of the interaction of non-verbal components of communication with verbal components in the process of creating a comic effect. The tasks of the master paper is to find out the main types of comic, giving the definition to humor, irony, sarcasm and satire, provide characteristics to the term “comic” as linguistic phenomenon, analyze verbal means of communication and define non-verbal means of communication, analyze the linguistic and customized means comic in the text, research the ways of creating comic effect by verbal and non-verbal means in native and foreign shows, films and TV. To solve problems, the following methods were used: The method of quasi-operative analyses of the material – for the establishment of belonging of text to those carrying s comic effect, as well as basic stylistic means applied in selected fragments. The method of pragmatic discourse analyses is to establish the value of influence on the addressee of TV discourse texts; the method of vocabulary definition is for the argumentation of the use of terms within the degree of work by means of lexicology. The method contextual analysis is for understanding comic situation in texts of television discourse; a method of comparable translation analyses is to determine the means of transferring the comic in Ukrainian. The scientifically novelty lies on that firstly there is analyses of creating comic effect by verbal and non-verbal means of communication on the background of foreign comic movies, shows. Also, there was the research of specificity of English humor. The material of master’s dissertation research is foreign talk-shows, jokes and interviews.